The Effectiveness of the City Government's Performance in Addressing the Widespread Student Fights in Padang City - Hisham, Muhammad Fazrul; Alhadi, Zikri (The Future of Education Journal, 2025)
Student brawls in Padang City have become an escalating social issue that disrupts public order and hinders the educational process. Data from the Civil Service Police Unit (Satpol PP) of Padang show significant fluctuations in the number of incidents over the past five years 48 cases in 2020, dropping to 2 in 2022, surging to 103 in 2023, and declining again to 29 in 2024, indicating that government interventions have not yet been consistently effective. This study aims to analyze the effectiveness of the Padang City Government’s policies in addressing student brawls and to identify factors hindering their implementation. Using a qualitative descriptive approach, data were collected through interviews, observations, and document studies involving local government officials, law enforcement, school representatives, students, parents, and community leaders. The findings reveal that the anti-brawl policy has been largely effective, supported by strong inter-agency coordination, character-building programs, and collaborative governance involving schools and communities. These efforts have reduced brawl incidents by over 85% between 2023 and 2025. However, several obstacles remain, including limited counseling facilities, unequal funding among schools, the negative influence of social media, and inadequate post-program monitoring. The study concludes that sustained policy effectiveness requires enhanced human resource capacity, community engagement, and long-term policy integration through the Regional Action Plan for Student Violence Prevention 2026–2030.